Current status and influencing factors of activation of older patients with chronic disease - Yiran, Zhu; Yan, Zhang; Lijun, Xing; Xizheng, Li; Xinjie, Zhang; Yutong, Tian (Frontiers in Public Health, 2024)
Objective We aimed to investigate the status and influencing factors of activation of older patients with chronic disease. Methods We conducted a cross-sectional study, using the general information questionnaire, Patient Activation Measure, the Chinese version of the e-Health Literacy Scale, and the Health Empowerment Scale for the Elderly with Chronic Disease. By the convenience sampling method, 289 older patients with chronic disease were selected from January to April 2023 in a Class A tertiary hospital in Zhengzhou. Results The mean score of the Patient Activation Measure for older patients with chronic disease was 65.94 ± 13.35. The association of influencing factors such as religion, family income, health empowerment, e-health literacy, and patient activation was investigated. Conclusion The patient activation of older patients with chronic disease was at a middle level. Patients without religion and from high-income families tended to have a higher level of patient activation. Improving health empowerment and e-health literacy levels promotes patient activation and enhances their self-health management ability.